Problem-Based Learning, Character Education Approach, and the Impacts on the Students’ Entrepreneurial Attitudes and Critical Thinking Skills - Dewi Maulinda (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2021)
This study aimed to determine the effect of implementing learning as well as producing a more effective, efficient, and meaningful economic learning through the application of problem-based learning in the Economic subject with a character education approach and its impact on the student's entrepreneurial attitudes and critical thinking skills. The research subjects were 80 students of the twelfth (XII) grade of Social Sciences in one madrasah in Jambi City. This research was a quasi-experiment with a control group design pretest-posttest design. The data collection used tests. The data analysis technique used a quantitative analysis. The results of the study indicated that there was an increase in student's character in the experimental class, entrepreneurial attitudes, and critical thinking skills compared to the control class group. Also the findings showed that students had a very good character in the experimental class, were able to think critically, and showed a truly entrepreneurial attitude compared to the control group.